Characterization of quartz crystal microbalance sensor for detection of bacteria inactivation after plasma treatment
This thesis presents a study of frequency response for detection of inactive bacteria using Quartz Crystal Microbalance sensor. The characteristics of frequency response towards detection of bacteria were discussed. The Escherichia coli bacteria with concentration x108 colony forming unit per milliliter were inactivated using new sterilization device which is atmospheric pressure plasma jet. A sensor device was constructed to monitor frequency response of bacteria in different condition by using 9 MHz quartz crystal. For detecting the bacteria sample, the sensor surface was prepared using Self-Assemble Monolayer technique together with Escherichia coli antibody as bioreceptor for antigen recognition. Quartz Crystal Microbalance sensor with gold electrodes were mounted in oscillator circuit and exposed to room temperature. The Transistor-transistor Logic oscillator circuit was utilized since it was able to drive the Quartz Crystal Microbalance sensor in air and liquid. Only one side of the crystal were exposed to the liquid sample by using static measurement. The measured of frequency response were observed in order to investigated the interfacial behavior of bacteria Escherichia coli on surface of sensor. The results show that the bacteria after inactivation have higher frequency shifting than bacteria before plasma treatment. The difference in frequency responses showed that bacteria inactivated by atmospheric plasma device have increment of mass. These situations are caused by several factors such as unspecific molecule presence inside inactive bacteria sample, types of bioreceptor, surface roughness and condition of electrode surface. The analysis also includes piezoelectric effects, experimental conditions and the characteristic of surface roughness. From average result of 10 sensors device utilized in the experiment, 8 were successful in bacteria detection. The detection also depends on condition of electrode surface. Moreover, this system has the ability to detect bacteria active and inactive in liquid situation.